1998
DOI: 10.1161/01.atv.18.7.1188
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Macrophage VEGF in Response to Oxidized LDL and VEGF Accumulation in Human Atherosclerotic Lesions

Abstract: Abstract-The interaction between macrophages and oxidatively modified low density lipoprotein (Ox-LDL) appears to play a central role in the development of atherosclerosis, not only through foam cell formation but also via the induction of numerous cytokines and growth factors. The current study demonstrated that Ox-LDL upregulated vascular endothelial growth factor (VEGF) mRNA expression in RAW 264 cells, a monocytic cell line, in a time-and concentration-dependent manner and that Ox-LDL stimulated VEGF prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 52 publications
(48 reference statements)
4
74
0
4
Order By: Relevance
“…Ramos et al 6 have shown that LPC also upregulates VEGF expression in RAW 264 cells. We have observed that LPC also induces VEGF expression in HCAECs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ramos et al 6 have shown that LPC also upregulates VEGF expression in RAW 264 cells. We have observed that LPC also induces VEGF expression in HCAECs.…”
Section: Discussionmentioning
confidence: 98%
“…Because Ox-LDL is abundant in atherosclerotic arterial walls and is critically involved in atherogenesis, we hypothesized that Ox-LDL might have a role in the expression of VEGF in atherosclerotic lesions. Ramos et al 6 have previously reported the induction of VEGF expression in a mouse macrophage-like cell line (RAW 264 cells) in response to Ox-LDL. The present study was compatible with their result and further revealed that Ox-LDLinduced upregulation of VEGF occurred not only in macrophages but also in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is a pleiotropic growth factor that seems to play a role in atherogenesis. It was shown that VEGF could participate in the progression of atherosclerosis by promoting macrophage chemotaxis 39) ; however, its activity was strongly related to plaque neovascularization, increasing vessel permeability and the promotion of inflammatory cell infiltration via new vessels into atherosclerotic plaque 27) . These effects of VEGF were not observed in our study, because no angiogenesis or neovascularization was detected in the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Other leucocytes, such as monocytes and T lymphocytes, produce VEGF when activated (Freeman et al, 1995;Harmey Human endometrial angiogenesis et al, 1998). There is evidence that in angiogenesis associated with inflammatory conditions, atherosclerosis and malignancy, extravasated leucocytes are a source of VEGF (Taichman et al, 1997;Harmey et al, 1998;Ramos et al, 1998). It is therefore possible that focal VEGF observed in human endometrium is located in intravascular leucocytes, which may have a role in endometrial angiogenesis by delivering VEGF directly to endothelial cells in vessels undergoing angiogenesis by non-sprouting mechanisms.…”
Section: Intravascular Vegf For Non-sprouting Angiogenesis In Endometmentioning
confidence: 99%